Nutrient management approach to improve productivity and profitability of pigeonpea (Cajanus cajan) in north east hill zones of India - SARKAR, SARMISTHA; DE, BIMAN; DAS, PARTHA; SAHA, DEBASREE; AWASTHI, DURGA PRASAD; PAUL, NILADRI; SEN, DEBASHISH (The Indian Journal of Agricultural Sciences, 2025)
The low yields of pigeonpea [Cajanus cajan (L.) Millsp] in the valleys of north eastern hill zones may be attributed to inadequate, unbalanced fertilization practices, and costly synthetic fertilizers application. These factors have had a negative impact on productivity, sustainability and soil health. The study was carried out during rainy (kharif) seasons 2022 and 2023 at the College of Agriculture, Lembucherra, West Tripura, Tripura to investigate effectiveness of organic matter in improving soil fertility while lowering reliance on synthetic fertilizers. A study was designed with eight treatments, viz. T1, 100% recommended dose of fertilizer (RDF) @20:60:40 kg/ha; T2, 50% RDF + phosphate solubilizing bacteria (PSB) @30 kg/ha; T3, 50% RDF + PSB @30kg/ha + Trichoderma @2.5 kg/ha; T4, 50% RDF + PSB @30 kg/ha + vermicompost (VC) @2.5 t/ha; T5, 50% RDF + PSB @30 kg/ha + Trichoderma @2.5 kg/ha + VC @2.5 t/ha; T6, 50% RDF + PSB @30 kg/ha + VC @5 t/ha; T7, 50% RDF + PSB @30 kg/ha + Trichoderma @2.5 kg/ha + VC @5 t/ha; T8, Control (farmers practice). The pigeon pea variety chosen for this study was PA- The experiment was laid out in a randomized block design (RBD) in three replications. Results indicated that applying vermicompost @5 t/ha and phosphorus-solubilizing bacteria @30 kg/ha markedly increased number of nodules (17.38) and leaf area index (5.54) at 90 and 120 days after sowing, respectively, with highest seed yield (1.90 t/ha) and stover yield (7.93 t/ha), when 50% of recommended doses had been replaced. Nutrient uptake, soil availability and microbial populations also showed the same trends. The greatest net return (80.43 × 103 ₹/ha) in the mentioned treatment also proves its economic viability. Hence, north-eastern hill farmers must adopt vermicompost and biofertilizers to substitute costly fertilizers for a higher return, while preserving soil health for future generations.